Błędy (orto)graficzne w rosyjskojęzycznych wiadomościach przesyłanych na kartach pocztowych - Dzienisiewicz, Daniel (Studia Rossica Posnaniensia, 2019)
The aim of the article is to analyse orthographic errors in Russian postcard messages from the second half of the 20th century. Nearly 240 orthographic errors retrieved from a corpus consisting of approximately 1000 Russian postcards have been classified and examined. The results of the study present the most common mistakes occurring in this type of correspondence.